QM/MM Study of the Dephosphorylation Mechanism of Adenosine 5′‐(β, γ‐Imido)triphosphate Catalyzed by Sulfolobus Tokodaii Hexokinase. Issue 6 (9th February 2018) - Wang, Jinhu; Wang, Zhiguo; Ling, Baoping; Yin, Hongqing; Zhang, Xian‐Man; Liu, Xuejing
Abstract: Adenosine triphosphate (ATP) bound hexokinase crystal structure is important for understanding the functions of hexokinase at the atomic level, but it is hard to obtain such complex because of the easy hydrolysis of ATP. Adenosine 5′‐(β, γ‐imido)triphosphate (AMP‐PNP) is a commonly used non‐hydrolysable ATP analogue for co‐crystallization with many proteins, but the AMP‐PNP function towards hexokinase is still unknown in the literature. In the present paper, we would like to report the dephosphorylation mechanisms of AMP‐PNP catalyzed by the wild‐type Sulfolobus tokodaii hexokinase ( St HK) and T116A mutant using quantum mechanical/molecular mechanical (QM/MM) method. The catalytic reactions proceed via a phosphate transfer, followed by a proton transfer in these models. Both St HK and T116A mutant catalyzed reactions are endothermic. The phosphate transfer reaction is the rate‐determining step, and their energy barriers are 15.95 and 22.71 kcal⋅mol −1 for St HK and T116A mutant, respectively. Comparison of the ATP dephosphorylation shows that the catalytic processes by the wild‐type and T116A mutated St HK are passivated. The passivation has been attributed to the linking –NH group of AMP‐PNP. The results are meaningful to a better understand of hexokinase and the functions of AMP‐PNP in cocrystallization. Abstract : As a nonhydrolysable analogue of ATP, AMP‐PNP plays an important role in the cocrystallization of hexokinase‐substrate complex. Current QM/MM study demonstrates the dephosphorylation mechanism of AMP‐PNP catalyzed by St HK at the atomic level and reveals the origin of passivation effects of AMP‐PNP towards St HK.